Platelet Pathogen Reduction Technologies Alter the MicroRNA Profile of Platelet-Derived Microparticles - Diallo, Idrissa; Benmoussa, Abderrahim; Laugier, Jonathan; Osman, Abdimajid; Hitzler, Walter E.; Provost, Patrick (Frontiers in Cardiovascular Medicine, 2020)
Despite improvements in donor screening, increasing efforts to avoid contamination and the spread of pathogens in clinical platelet concentrate (PCs), the risks of transfusion-transmitted infections remain important. Relying on an ultraviolet photo activation system, pathogen reduction technologies (PRTs), such as Intercept and Mirasol, utilize amotosalen and riboflavin (vitamin B2), respectively, to mediate inactivation of pathogens nucleic acids. Although they are expected to increase the safety and prolong the shelf-life of clinical PCs, these PRTs might affect the quality and function of platelets, as recently reported. Upon activation, platelets release microparticles (MPs), which are involved in intercellular communications and regulation of gene expression, thereby mediating critical cellular functions. Here, we have used small RNA sequencing (RNA-Seq) to document the effect of PRT treatment on the microRNA profiles of platelets and derived MPs. PRT treatment did not affect the microRNA profile of platelets. However, we observed a specific loading of certain microRNAs into platelet MPs, which was impaired by treatment with Intercept or its Additive solution (SSP+). Whereas Intercept had an impact on the microRNA profile of platelet-derived MPs, Mirasol did not impact the microRNA profile of platelets and derived MPs, compared to non-treated control. Considering that platelet MPs are able to transfer their microRNA content to recipient cells, and that this content may exert biological activities, those findings suggest that PRT treatment of clinical PCs may modify the bioactivity of the platelets and MPs to be transfused and argue for further investigations into PRT-induced changes in clinical PC content and function.